Severe periodontitis enhances macrophage activation via increased serum lipopolysaccharide - Pussinen, Pirkko J; Vilkuna-Rautiainen, Tiina; Alfthan, Georg; Palosuo, Timo; Jauhiainen, Matti; Sundvall, Jouko; Vesanen, Marja; Mattila, Kimmo; Asikainen, Sirkka (Arteriosclerosis, thrombosis, and vascular biology, 2004)
In periodontitis, overgrowth of Gram-negative bacteria and access of lipopolysaccharide (LPS) to circulation may activate macrophages leading to foam cell formation. We investigated whether periodontal treatment affects proatherogenic properties of low-density lipoprotein (LDL) and, thus, macrophage activation. LDL was isolated and characterized before and after treatment from 30 systemically healthy patients with periodontitis. Production of cytokines and LDL cholesteryl ester (LDL-CE) uptake by macrophages (RAW 264.7) was determined. Baseline periodontal variables correlated positively with serum LPS and C-reactive protein concentrations, as well as macrophage cytokine production and LDL-CE uptake. LPS concentration correlated positively with serum concentration of oxidized LDL and cytokine production. Higher cytokine production and LDL-CE uptake were induced by LDL isolated from patients with elevated number of affected teeth before treatment. Patients with serum LPS concentrations above the median (0.87 ng/mL) at baseline had higher serum high-density lipoprotein (HDL) cholesterol (baseline versus after treatment, 1.30+/-0.19 versus 1.48+/-0.28 mmol/L; P=0.002) and HDL/LDL ratio (0.31+/-0.01 versus 0.34+/-0.10; P=0.048), but lower serum LPS concentration (1.70+/-0.49 versus 0.98+/-0.50 ng/mL; P=0.004) and autoantibodies to beta2-glycoprotein I (0.11+/-0.06 versus 0.09+/-0.04 ELISA units; P=0.022) after treatment. Our results suggest that in systemically healthy patients, the infected/inflamed area in periodontitis is associated with macrophage activation via increased serum LPS concentration.